Taking Stock: Credit measures in monetary transmission - Stefan Behrendt (Friedrich Schiller University Jena, 2016)
Empirical research on the monetary transmission mechanism considering credit developments is almost exclusively limited to the amount of outstanding credit in an economy. Two issues arise out of this. First, stock-flow inconsistencies might occur. Second, the change of the outstanding amount of credit on banks balance sheets does not consist only of new lending activity, but also incorporates other factors. As central banks should predominantly be focused on the amount of newly created credits in an economy while analysing the impact of monetary policy towards lending activity, using the change in the stock of lending can lead to distorted results, because of the incorporation of data on maturing loans, revaluations, securitization, and write-offs into this variable. The majority of existing credit channel literature does not really account for these issues. This paper makes a case to better caption new lending activity in monetary policy research. What is shown in this paper is that empirical investigations might lead to differing results when accounting for the other factors in the stock data. Central bank policy might therefore be biased.
Keywords: C18; C82; E51; E52; 330; bank lending; credit channel; monetary transmission